Fundamental concept of cryopreservation using Dendrobium sonia-17 protocorm-like bodies by encapsulation-dehydration technique - Subramaniam, Sreeramanan; Sinniah, Uma Rani; Khoddamzadeh, Amir Ali; Periasamy, Suranthran; James Antony, Jessica Jeyanthi (Academic Journals, 2011)
This study was carried out to evaluate the potential of using the encapsulation-dehydration technique on cryopreservation protocorm-like bodies (PLBs) of Dendrobium sonia-17. The survival of the PLBs was assessed based on the effects of 4 dehydration periods (0, 1, 3 and 5 h) and 4 different concentrations of 24-h sucrose pretreatment (0, 0.3, 0.5 and 0.7 M). Upon dehydration, moisture content was determined and the PLBs were evaluated for survival using absorbance values from 2, 3,5- triphenyltetrazolium chloride (TTC) assay at 530 nm and regeneration observations. Moisture content declined with the dehydration time, but the decline was not significant for encapsulated PLBs. All cryopreserved PLBs gave very low survival irrespective of the dehydration period. The best survival percentage in the cryopreservation of the PLBs of Dendrobium sonia-17 was obtained when the combination of 0.5 M sucrose pretreatment and 3 h dehydration time was applied in the experiment.